2013
DOI: 10.1088/0004-637x/775/1/35
|View full text |Cite
|
Sign up to set email alerts
|

On the Impact of Three Dimensions in Simulations of Neutrino-Driven Core-Collapse Supernova Explosions

Abstract: We present 1D, 2D, and 3D hydrodynamical simulations of core-collapse supernovae including a parameterized neutrino heating and cooling scheme in order to investigate the critical core neutrino luminosity (L crit ) required for explosion. In contrast to some previous works, we find that 3D simulations explode later than 2D simulations, and that L crit at fixed mass accretion rate is somewhat higher in 3D than in 2D. We find, however, that in 2D L crit increases as the numerical resolution of the simulation inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
196
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(230 citation statements)
references
References 79 publications
33
196
1
Order By: Relevance
“…The systematic behaviors that we found, as shown in Figure 13 for example, might be subject to change quantitatively. At least, our 2D results showing that higher numerical resolutions lead to slower evolution of the shock radius and the diagnostic explosion energy, are consistent with Couch (2013) and Takiwaki et al (2014). A systematic resolution study including a detailed comparison between different numerical codes, schemes, and setups should be done urgently, which we leave for future work.…”
Section: Conclusion and Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The systematic behaviors that we found, as shown in Figure 13 for example, might be subject to change quantitatively. At least, our 2D results showing that higher numerical resolutions lead to slower evolution of the shock radius and the diagnostic explosion energy, are consistent with Couch (2013) and Takiwaki et al (2014). A systematic resolution study including a detailed comparison between different numerical codes, schemes, and setups should be done urgently, which we leave for future work.…”
Section: Conclusion and Discussionsupporting
confidence: 76%
“…Further global simulation, taking account of gravitational energy of an envelope and nuclear energy released via recombination process behind the shock, is necessary to determine the final explosion energy ( Figure 15). Moreover, the finding of this study should be reexamined by 3D models (Hanke et al 2012;Dolence et al 2013;Couch 2013;Couch & O'Connor 2014;, in which neutrino transport is appropriately solved (see, discussions in Hanke et al 2013;Nagakura et al 2014;Mezzacappa et al 2014). It is also important to study the impacts of the precollapse non-spherical structures (e.g., Arnett & Meakin 2011) on fostering the shock revival (e.g., Couch & Ott 2013).…”
Section: Conclusion and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…They increase the effective neutrino heating efficiency because rising fluid elements have lower neutrino emissivities after adiabatic expansion, reducing losses due to neutrino cooling, and the non-radial motions increase the dwell time of fluid elements in the gain region, thereby increasing the time they are subject to neutrino heating. In addition, as was pointed out by Burrows et al (1995), Dolence et al (2013), Couch (2013a) and demonstrated more quantitatively by Murphy et al (2013) and Couch & Ott (2015), the rising turbulent convective plumes exerts a dynamical pressure on the shock aiding its expansion. We will discuss these effects in the context of our models in more detail below.…”
Section: Development Of Instabilities and Asphericitymentioning
confidence: 71%
“…Imposing symmetries on simulations of CCSNe can have significant consequences for their evolution (e.g., Hanke et al 2012;Couch 2013;Murphy et al 2013). Detailed spherically symmetric one-dimensional (1D) simulations do not explode (Liebendörfer et al 2001), except when particular low-mass progenitor models are used (e.g., Fischer et al 2010;Hüdepohl et al 2010).…”
Section: Introductionmentioning
confidence: 99%